[Retracted Article] Extraterritorial obligations of States on economic, social, cultural rights and development operations - Liakopoulos, Dimitris (Homa Publica - Revista Internacional de Derechos Humanos y Empresas, 2019)
The Editorial Team of Homa Publica - Revista Internacional de Derechos Humanos y Empresas - has proceeded to retract the research because the scientific article has been published by another scientific journal, (ii) terms identified plagiarism in the paper.